Knowing and asserting - Williamson, T (Duke University Press, 1996)
This paper aims to identify the constitutive rule(s) of assertion, conceived by analogy with the rules of a game. That assertion has such rules is by no means obvious; perhaps it is more like a natural phenomenon than it seems. One way to find out is by supposing that it has such rules, in order to see where the hypothesis leads and what it explains. That will be done here. The hypothesis is not perfectly clear, of course, but we have at least a crude conception of constitutive rules, which we may refine as we elaborate the hypothesis. Although no attempt will be made here to define ‘rule’, some remarks on constitutive rules will focus the discussion.